ISLAMIC ECONOMIC REVIEW OF CONSUMPTION: A SYSTEMATIC LITERATURE REVIEW APPROACH - Sadali, Ayatullah; Hermawan Adinugraha, Hendri; Shulthoni, Muhammad (JIM : Journal Of International Management, 2024)
This research analyzes consumption studies from an Islamic economic perspective and a literature review perspective. The research method uses a qualitative type with a systematic literature review approach. The research results obtained from this literature review found that consumption is human nature to maintain life and is a very vital part of economic activity for human life. Islamic consumption theory limits consumption based on the concept of wealth and various types of consumption by Sharia principles for sustainability and the welfare of the ummah. Rapid economic growth and technological developments are causing changes in people’s consumption patterns. The main difference in consumption patterns in Islamic and conventional economics lies in the intention and approach to meeting life’s needs. Intentions and consumption methods to meet needs are critical in the Islamic economic system. Islamic economics does not place materialism as a guide to human life. Islam does not recognize the principle of materialism as conventional economics places consumption in the perspective of mere worldly satisfaction.